5(h+3)+2(h-2)=11-3(12-5h)

Simple and best practice solution for 5(h+3)+2(h-2)=11-3(12-5h) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(h+3)+2(h-2)=11-3(12-5h) equation:


Simplifying
5(h + 3) + 2(h + -2) = 11 + -3(12 + -5h)

Reorder the terms:
5(3 + h) + 2(h + -2) = 11 + -3(12 + -5h)
(3 * 5 + h * 5) + 2(h + -2) = 11 + -3(12 + -5h)
(15 + 5h) + 2(h + -2) = 11 + -3(12 + -5h)

Reorder the terms:
15 + 5h + 2(-2 + h) = 11 + -3(12 + -5h)
15 + 5h + (-2 * 2 + h * 2) = 11 + -3(12 + -5h)
15 + 5h + (-4 + 2h) = 11 + -3(12 + -5h)

Reorder the terms:
15 + -4 + 5h + 2h = 11 + -3(12 + -5h)

Combine like terms: 15 + -4 = 11
11 + 5h + 2h = 11 + -3(12 + -5h)

Combine like terms: 5h + 2h = 7h
11 + 7h = 11 + -3(12 + -5h)
11 + 7h = 11 + (12 * -3 + -5h * -3)
11 + 7h = 11 + (-36 + 15h)

Combine like terms: 11 + -36 = -25
11 + 7h = -25 + 15h

Solving
11 + 7h = -25 + 15h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-15h' to each side of the equation.
11 + 7h + -15h = -25 + 15h + -15h

Combine like terms: 7h + -15h = -8h
11 + -8h = -25 + 15h + -15h

Combine like terms: 15h + -15h = 0
11 + -8h = -25 + 0
11 + -8h = -25

Add '-11' to each side of the equation.
11 + -11 + -8h = -25 + -11

Combine like terms: 11 + -11 = 0
0 + -8h = -25 + -11
-8h = -25 + -11

Combine like terms: -25 + -11 = -36
-8h = -36

Divide each side by '-8'.
h = 4.5

Simplifying
h = 4.5

See similar equations:

| 2(m-3)=8 | | Y-5=-8/3(x-2) | | 9+2v=-v | | Y=65x+0.10 | | 2.464cosx-x=2.5843 | | 7x+9=3x+8 | | -a/10=-16 | | a-3b+2c=-16 | | Y=65+0.10 | | 3(w+1)=9 | | 2.464cosx-x=205843 | | 47-3=6y | | 6x-79=12x+47 | | 1/3y-6=1/10y | | 6(2f+4)=2(3f-6) | | x+6*x-1= | | 1c+4.8=8 | | 2/3x-18=6 | | 7(x+8)=(7x+42) | | 2x-7=x-7 | | T/15=5 | | x(x+2x+x(x-1)+1-4)=0 | | u=2x-5 | | 15-2x=10-5x | | 6(-2+a)-(-5+a)-3(9+a)=0 | | 3n+7-n-3=n | | 6p+1=3[2p+1] | | P=(5t/6)-4 | | 5t+11=5 | | 6a+3b+c=-23 | | (-8)/(-1)/(1)/(4) | | 3[g-1]-7=3g+4 |

Equations solver categories